2015
DOI: 10.1109/led.2015.2454535
|View full text |Cite
|
Sign up to set email alerts
|

Steep-Slope Metal–Insulator-Transition VO2Switches With Temperature-Stable High $I_{\mathrm{{\scriptscriptstyle ON}}}$

Abstract: This work reports a detailed experimental investigation of the slope of the current switching between OFF and ON states exploiting the metal-insulator-transition in vanadium dioxide devices. The reported devices are CMOS compatible 2-terminal switches. We experimentally demonstrate for the first time the very little dependence on temperature of the steep slope of these switches, ranging from 0.24 mV/decade at room temperature, to 0.38 mV/decade at 50°C. The fabricated devices show excellent on-state conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A load resistance R L is used to allow a current flow high enough to reach the power threshold of the VO 2 switch 43 . The value of R L is selected in order to have R VO2_OFF  >>  R L  >>  R VO2_ON , where R VO2_OFF is the resistance of the MIT switch in the insulating state and R VO2_ON is the resistance in the metallic state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A load resistance R L is used to allow a current flow high enough to reach the power threshold of the VO 2 switch 43 . The value of R L is selected in order to have R VO2_OFF  >>  R L  >>  R VO2_ON , where R VO2_OFF is the resistance of the MIT switch in the insulating state and R VO2_ON is the resistance in the metallic state.…”
Section: Resultsmentioning
confidence: 99%
“…VO 2 holds great potential for beyond CMOS electronics because the MIT can be induced by electrical excitations, enabling applications based on volatile resistive switching. The VO 2 -based MIT switch in 2-terminal configuration shows interesting properties such as abrupt increase in current with applied voltage 23–31 , fast switching time 3234 , high reliability 35, 36 , negative differential resistance 3740 , memristive switching 41, 42 and low temperature dependence of transition dynamics 43, 44 . However, the main drawback of the 2-terminal MIT switch is the relatively high leakage current I OFF due to the small bandgap of VO 2 in the insulating state.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers, including us [56], have demonstrated that the effect of electrical switching occurs due to MIT, when the current passing through the VO 2 structure heats it with Joule heat to a temperature T t . There is a strong dependence of the threshold switching parameters on the ambient temperature T 0 [46]. An increase in T 0 leads to a decrease in the threshold voltage U th and, at T 0~Tt , the switching effect will be suppressed since the VO 2 channel will always be in a highly conductive state.…”
Section: Discussionmentioning
confidence: 99%
“…[87] These gains come from aggressive improvements to circuit design, component integration, and data parallelism, as well as power-management schemes that put unused circuits into low-power states whenever possible. [90] To address such fundamental problem, new classes of steep-slope switches, [91] e.g., Tunnel FETs, [92] nanoelectromechanical relay, [93] negative capacitance FETs, [94] and metalinsulator-transition, [95] have emerged to drastically lower the supply voltage (V DD < 0.3 V) and threshold voltage (V T < 0.1 V) to a level which cannot be reached by CMOS based on 2015 ITRS report. Of course, as with any exponential trend, this one will eventually end, active power will still be hostage to the physics behind the slowdown in the ability to shrink transistors.…”
Section: Summary and Prospectsmentioning
confidence: 99%